Study on the strength of laminated polyurethane-steel joints - Datta, J.; Haponiuk, J.; Głowińska, E.; Durczak, Ł. (Polimery, 2012)
Tearing strength of laminated polyurethane-steel joints was examined. Polyurethane system and the conditions of its application on steel elements were developed. Laminate samples were formed by casting the polyurethane system onto the flats with different surface roughness, which were placed in a steel mould coated with a layer of bonding agents. The effects of: the degree of flat surface development, time of the solvent evaporation from the adhesive binding the materials, the adhesive layer thickness as well as the addition of adhesion promoter and the sample seasoning time on the mechanical strength of polyurethane-steel joint were evaluated.